Re/conceptualising time and temporality: an exploration of time in higher education. Issue 6 (2nd November 2018) - Bennett, Anna; Burke, Penny Jane
ABSTRACT: In this paper we deconstruct hegemonic conceptions of time in higher education. Drawing on a recent project, we argue that limiting assumptions about time dominate notions of student capability and prospects of success. The paper reveals how the conceptualisation of time is constituted within a framework that individualises and decontextualises difficulties. Within this frame, socio-cultural elitism is left largely unchallenged, with many students left out and misrecognised as purely lacking capability and commitment. Rethinking simple distinctions between 'time' and 'temporality', we consider ways to broaden understandings to enable a more inclusive and 'inventive' system. We apply a Foucauldian analysis to argue that we co-construct the future in the very ways that we react to the present and think about the past. We must recognise that the way we work in the present is how we create the future. Our everyday actions, assumptions and reactions re/produce our futures.